PENERAPAN STRATEGI DIGITAL MARKETING PADA UMKM DI MASA PANDEMI COVID19 (Studi Pada Mebel Putra Jaya Desa Spait) - Muhamat Soleh; Hendri HAN (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
The facts regarding the development of umkm in the city of pekalongan are widely found in communities that shop online. It isa problem for small middle-class micro businesses to survive and help Indonesia's economy in the current covid-19 pandemic. So the purpose of this study is to know the implementation of digitisation and digital marketing strategies at umkm Mebel Putra Jaya pekalongan. In the study a qualitative approach with a descriptive mode type data using data collection techniques for the study using interviews, documentaries, and observations.